Teaching English in Multilingual and Multicultural Contexts in Nepal - Bhandari, Bhim Lal (Tribhuvan University Journal, 2016)
English is being taught in diverse contexts around the globe. Teaching of English in multilingual and multicultural contexts in Nepal is one of the major challenges in ELT. The majority of classes in Nepal consist of linguistic and cultural diversity where students need to have different learning materials, methodologies and learning styles which help them minimize the problems of interaction and comprehension. This article presents both challenges and opportunities of teaching English in multicultural and multilingual contexts. The problems created by linguistically heterogeneous learners and attitude of parents towards multilingual education are the major challenges for its effective implementation. Moreover, the problems of teachers and students are being addressed in this article along with some suggestions for teachers to solve them and make ELT more effective, better and easier.